Effect of Leaf Color Chart (LCC)-based Nitrogen Application in Wheat on Available Nutrients and Enzyme Activity in Soil: Leaf color chart-based nitrogen application in wheat - Gulshan; Yadav, Rajpaul; Raj, Dev; Vashisth, Usha; Kumari, Kiran (Journal of Soil Salinity and Water Quality, 2025)
Nitrogen management in wheat is becoming important to counteract the adverse effect of excess application of N on environment as well as on economics of the farmers. We examined the effect of different N recommendation approaches on available N fraction in the soil, urease activity at different growth stages of wheat and nutrient use efficiencies in South-West Haryana. Results showed that the available N content varied significantly during the different crop growth stages of wheat. The highest N content was reported in treatment where N was applied on the basis of STCR approach. However, the available N content in leaf color chart (LCC) based treatment was equivalent to RDN treatment at the harvest of the crop, showing 30% N fertilizer saving without sacrificing the grain yield. The trend of urease enzyme activity was followed the N availability. The activity of urease was found significantly maximum in the treatment where N was applied on the basis of STCR equation in all growth stages except at 20 and 40 days after sowing (DAS). Urease activity in LCC based treatment noticed almost equivalent as observed under RDN application after harvest of the wheat. The significantly highest amount of available P and K was recorded in the treatment where LCC guided one split of N was applied.